Synthetic Approaches to Complex Organic Molecules in the Cold Interstellar Medium - Herbst, Eric; Garrod, Robin T. (Frontiers in Astronomy and Space Sciences, 2022)
The observation and synthesis of organic molecules in interstellar space is one of the most exciting and rapidly growing topics in astrochemistry. Spectroscopic observations especially with millimeter and submillimeter waves have resulted in the detection of more than 250 molecules in the interstellar clouds from which stars and planets are ultimately formed. In this review, we focus on the diverse suggestions made to explain the formation of Complex Organic Molecules (COMs) in the low-temperature interstellar medium. The dominant mechanisms at such low temperatures are still a matter of dispute, with both gas-phase and granular processes, occurring on and in ice mantles, thought to play a role. Granular mechanisms include both diffusive and nondiffusive processes. A granular explanation is strengthened by experiments at 10 K that indicate that the synthesis of large molecules on granular ice mantles under space-like conditions is exceedingly efficient, with and without external radiation. In addition, the bombardment of carbon-containing ice mantles in the laboratory by cosmic rays, which are mainly high-energy protons, can lead to organic species even at low temperatures. For processes on dust grains to be competitive at low temperatures, however, non-thermal desorption mechanisms must be invoked to explain why the organic molecules are detected in the gas phase. Although much remains to be learned, a better understanding of low-temperature organic syntheses in space will add both to our understanding of unusual chemical processes and the role of molecules in stellar evolution.